Preclinical pharmacokinetic, biodistribution, toxicology, and dosimetry studies of 111In-DTPA-human epidermal growth factor: an auger electron-emitting radiotherapeutic agent for epidermal growth factor receptor-positive breast cancer. - Reilly, R; Chen, P; Wang, J; Scollard, D; Cameron, R; Vallis, K (2006)
UNLABELLED: Our objective was to evaluate the pharmacokinetics, normal tissue distribution, radiation dosimetry, and toxicology of human epidermal growth factor (hEGF) labeled with (111)In ((111)In-diethylenetriaminepentaacetic acid [DTPA]-hEGF) in mice and rabbits. METHODS: (111)In-DTPA-hEGF (3.6 MBq; 1.3 or 13 microg) was administered intravenously to BALB/c mice. The blood concentration-time data were fitted to a 3-compartment model. Acute toxicity was studied with female BALB/c mice at 42 times the maximum planned human dose (MBq/kg) or with New Zealand White rabbits at 1 times the maximum planned human dose (MBq/kg) for a phase I clinical trial. Toxicity was evaluated by monitoring body weight, by determination of hematology and clinical biochemistry parameters, and by morphologic examination of tissues. Radiation dosimetry projections in humans were estimated on the basis of the residence times in mice by use of the OLINDA version 1.0 computer program. RESULTS: The largest amounts of radioactivity were taken up by the liver (41.3 +/- 7.8 [mean +/- SD] percentage injected dose [%ID] at 1 h after injection and decreasing to 4.9 +/- 0.3 %ID at 72 h after injection) and kidneys (18.6 +/- 0.8 %ID at 1 h and decreasing to 4.5 +/- 0.2 %ID at 72 h after injection). (111)In-DTPA-hEGF was cleared rapidly from the blood, with a half-life at alpha-phase of 2.7-6.2 min and a half-life at beta-phase of 24.0-36.3 min. The half-life of the long terminal phase could not be accurately determined. The volume of distribution of the central compartment was 340-375 mL/kg, and the volume of distribution at steady state was 430-685 mL/kg. There was no significant difference in the ratio of body weight at 15 d to pretreatment weight for mice administered (111)In-DTPA-hEGF (1.02 +/- 0.01) and mice administered unlabeled DTPA-hEGF (1.01 +/- 0.01). Erythrocyte, leukocyte, and platelet counts and serum alanine aminotransferase and creatinine levels remained in the normal ranges. No morphologic changes were observed by light microscopy in any of 19 tissues sampled. Minor morphologic changes in the liver were observed by electron microscopy. The projected whole-body dose in humans was 0.19 mSv.MBq(-1). The projected doses to the liver, kidneys, and lower large intestine were 0.76, 1.82, and 1.12 mSv.MBq(-1), respectively. CONCLUSION: (111)In-DTPA-hEGF was safely administered to mice and rabbits at multiples of the maximum dose planned for a phase I trial in breast cancer patients.